Efektifitas Model Pembelajaran Kooperatif Tipe STAD dan NHT Berbantuan Alat Peraga Sistem Pernapasan Manusia Terhadap Motivasi dan Hasil Belajar Kognitif Siswa - Nonci Melinda Uki (Biota, 2018)
This study aims to the effectiveness of cooperative learning model type STAD, NHT and Conventional aided props to the motivation and learning outcomes of students on the material the respiratory system in humans. The method used Quasi-Experiment with design Nonequivalent control group design involving three classes, which use the model of STAD, NHT and Conventional. Data were collected through test result of learning and motivation questionnaire were analyzed descriptively (Anova) at α = 0.05. The results showed that the learning outcomes STAD group (36.47), NHT group (41.20) and Conventional (34.84). It can be concluded that there are differences between the models STAD learning outcomes, NHT and Conventional on the subject of the respiratory system in humans. This shows that the use of cooperative learning model NHT more effective in improving student learning outcomes compared with STAD and conventional models. The third model applied learning effectively increase student motivation.